Review of the little-known western Nearctic fly genus Philetus Melander (Diptera: Empididae), with a discussion of its phylogenetic assignment - Cumming, Jeffrey M.; Brooks, Scott E.; Sinclair, Bradley J. (Zootaxa, 2016)
The western North American empidid genus Philetus Melander is reviewed, including redescription of the two included species, P. memorandus Melander and P. schizophorus Melander. A lectotype is designated for P. schizophorus. The        distributions of both species are mapped and the male terminalia are illustrated. The female of P. schizophorus is discovered for the first time through comparison of COI mitochondrial DNA barcode sequences. The phylogenetic assignment of  Philetus within the Empididae is discussed based on a reinterpretation of male terminalia homologies.